The Effect of Business Strategy and CSR in Influencing Tax Avoidance - Sibarani, Maruhum Sanni; Tarmidi, Deden (Research Horizon, 2024)
This study aims to determine and examine the effect of business strategy and Corporate Social Responsibility on tax avoidance in Manufacturing Companies listed on the Indonesia Stock Exchange in the period 2019 to 2022. Using purposive sampling method and panel data multiple regression, the results of this study indicate that the combined business strategy carried out by the company has no influence on tax avoidance, but separately with the expansion test it is found that the prospector business strategy has a negative effect on tax avoidance, while corporate social responsibility has a positive effect on tax avoidance. These results explain that companies that use prospector business strategies tend to reduce tax avoidance actions, and CSR costs are used by companies to avoid paying taxes.